Enhancing the Role of Advanced Independent Workforce Mentors in Indonesia Through Dual Monitoring and Evaluation - Lukman Hakim, Dani; Fernando, Agus; Satwhikawara, Rachmi; Veronica, Selly; Wishnu Perdana Widiputra, Anthonius (International Journal Of Community Service, 2025)
The Advanced Independent Workforce (AIW) program plays a pivotal role in facilitating the development of micro and small enterprises in Indonesia. Nonetheless, various challenges, including inconsistent mentorship and limited evaluation mechanisms, impede its overall effectiveness. In response to these issues, a Dual Monitoring and Evaluation (DME) system was implemented to enhance the role of AIW mentors. This system comprises one-on-one meetings aimed at delivering personalized guidance, as well as onsite monitoring and evaluation to assess real-time business progress and operational challenges. This initiative was executed across multiple provinces in Indonesia, engaging mentors, mentees, and relevant stakeholders. The findings indicate that the DME system significantly enhances mentor effectiveness, bolsters business sustainability, and improves problem-solving capabilities. The one-on-one meetings afforded structured feedback and capacity-building opportunities for mentors, while onsite evaluations facilitated direct observation and timely interventions for mentees. The integration of direct engagement and field-based evaluation not only strengthened mentorship strategies but also increased mentee confidence and promoted adaptive business practices. This study underscores the importance of a structured mentoring model in workforce development and recommends the expansion of DME coverage, the incorporation of digital tools, and the development of standardized evaluation metrics. This approach presents a scalable model for analogous economic empowerment programs, thereby ensuring sustainable mentorship and the success of enterprises.